Influence of Education and Work Experience on Work Motivation and Job Performance at Branch Office of BANK J Trust Bank Surabaya - Ani Wulandari (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2017)
The purpose of this study is to analyze the Effect of Education and Work Experience on Work Motivation and Job Performance in J TRUST BANK Branch Office Surabaya. The result showed that education has positive and significant effect on work motivation, seen from t count (3,866) > value of t table (1,682), it can be said that there is a partially significant influence from educational variable to work motivation in J TRUST BANK branch in Surabaya amounting to 46,1%. Work experience has a positive and significant effect to work motivation, seen from t count (3,150)> from t table (1,682), it can be said that there is a partially significant influence from work experience variable to work motivation in J TRUST BANK branch in Surabaya which equal to 37,5%. Education has a positive and significant effect to work performance, seen from t count (2,764) > from t table (1,682), it can be concluded that there is a partially significant influence from educational variable to achievement of work atJ TRUST BANK Branch in Surabaya at 35.7%.